Improving the hardware and software for control of normalized parameters of production factors - Поперека, Екатерина Дмитриевна; Костенко, Виталий Леонидович; Зайцева, Дарья Игоревна; Тыманюк, Константин Сергеевич (Technology audit and production reserves, 2016)
The results of improving the hardware and software for control of normalized parameters of sanitary and hygienic factors of the workplace are shown based on previously developed using «Dolphin» type measuring stand. Software and hardware of computer systems for control of the normalized parameters of production factors are studied. The issues for empowerment of the measuring equipment through the use of mDAQ12 data acquisition microsystem and expansion of the range of the sensor are considered. A block diagram of the hardware and software of the normalized parameters control is developed. Development of the hardware is completed. mDAQ12 data acquisition microsystem is used as the basis in return «Dolphin» type measuring stand used in previous studies. Development of a flexible software using LabVIEW platform is made that enables operational control of normalized parameters of production factors, by reducing time to conduct measurement and processing of measurement results of 9 physical factors, namely, noise, vibration, air velocity, temperature and relative humidity, pressure, infrared illumination and monitoring of air quality. The adopted development concept allows creating a hardware and software package with the possibility of reconfiguration. The proposed hardware and software also allows at least an order reducing weight and overall dimensions and improve economic performance, as well as halving the time and cost of software development by applying LabWIEV platform. The results of the control simulation are shown. Research can be practically used for automated control of the sanitary and hygienic factors of production industry.